2013
DOI: 10.1002/ajh.23584
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus is a potential risk factor for late‐onset hemorrhagic cystitis following allogeneic hematopoietic stem cell transplantation

Abstract: Late-onset hemorrhagic cystitis (LOHC) is a common complication following allogeneic hematopoietic stem cell transplantation (allo-HSCT) and is primarily associated with viral infection. We prospectively quantified cytomegalovirus (CMV), BK virus (BKV), and adenovirus in urine and plasma using Q-RT-PCR in 50 consecutive patients to define the relationship between virus and LOHC. Of the 50 patients, 21 developed LOHC at a median of 29 days (range 4-64 days), with a cumulative incidence of 42% (67.1%). The cumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 41 publications
2
23
1
1
Order By: Relevance
“…Additional co-reactivations/infections with other viruses reflects the immunosuppressive status as known risk factor for BKPyV cystitis [11]. Accordingly, in our cohort 59% of the BKPyV cases also had CMV reactivation within the 1st 100 days, which is in line with findings by others showing that 59% of patients with CMV [12]. aGvHD is a known risk factor for viral reactions [13], which was also verified here, as 64% of all BKPyV cases suffered from aGvHD II-IV°and 73% received steroid-medication (≥5 mg/d) at the time of BKPyV cystitis.…”
supporting
confidence: 92%
“…Additional co-reactivations/infections with other viruses reflects the immunosuppressive status as known risk factor for BKPyV cystitis [11]. Accordingly, in our cohort 59% of the BKPyV cases also had CMV reactivation within the 1st 100 days, which is in line with findings by others showing that 59% of patients with CMV [12]. aGvHD is a known risk factor for viral reactions [13], which was also verified here, as 64% of all BKPyV cases suffered from aGvHD II-IV°and 73% received steroid-medication (≥5 mg/d) at the time of BKPyV cystitis.…”
supporting
confidence: 92%
“…Several risk factors alone or in association with BKPyV have been reported to contribute to the development of HC, including GVHD, chemotherapeutics and supportive medications, and other bacterial or viral infections . In the present study, patients affected by HC showed a higher incidence of CMV reactivations (>1000 IU/mL), which has been previously correlated with BKPyV‐associated HC .…”
Section: Discussionsupporting
confidence: 79%
“…Fittingly, patients detected to be BKPyV positive in urine only did not develop clinical relevant HC. 15,30,[32][33][34][35][36] In the present study, patients affected by HC showed a higher incidence of CMV reactivations (>1000 IU/mL), which has been previously correlated with BKPyV-associated HC. 15 In line with the more protracted course of higher-grade HC (above) in conjunction with lymphocyte recovery and GVHD, patients with HC of grade II/III developed significantly more often GVHD after day+100 than those with low-grade HC.…”
Section: Discussionmentioning
confidence: 63%
“…Age of the HCT recipient > 7 years is regarded as a risk factor for BKV reactivation [20]. CMV or human herpesvirus 6 (HHV6) viremia facilitates BKV hemorrhagic cystitis [21].…”
Section: Discussionmentioning
confidence: 99%